2011
DOI: 10.4021/jnr20w
|View full text |Cite
|
Sign up to set email alerts
|

Functional Level During the First Year After Moderate and Severe Traumatic Brain Injury: Course and Predictors of Outcome

Abstract: Background: The objective of this study was to describe the functional level during the first year after moderate and severe traumatic brain injury (TBI), and to evaluate the predictive impact of preinjury and injury-related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
1
4
1
Order By: Relevance
“…These recent results are typical for the TBI population routinely observed at the Kessler Institute. The FIM scores from the Kessler TBI population were lower compared to another study 76 and to the reported total FIM from all sixteen sites within the TBI Model Systems Database (52 for rehabilitation admission, N=9861; 92 for rehabilitation discharge, N=9781). 74 These data suggest that TBI in-patients from Kessler on average may be more severely affected, with pathology in the moderate-severe rather than mild TBI range.…”
Section: Discussioncontrasting
confidence: 64%
“…These recent results are typical for the TBI population routinely observed at the Kessler Institute. The FIM scores from the Kessler TBI population were lower compared to another study 76 and to the reported total FIM from all sixteen sites within the TBI Model Systems Database (52 for rehabilitation admission, N=9861; 92 for rehabilitation discharge, N=9781). 74 These data suggest that TBI in-patients from Kessler on average may be more severely affected, with pathology in the moderate-severe rather than mild TBI range.…”
Section: Discussioncontrasting
confidence: 64%
“…The functional level was assessed by GOSE and was found to improve significantly during the first 6 months of injury. This finding concurred with that in several previous studies (deGuise et al, 2008; Sandhaug et al, 2011; Sandhaug et al, 2015; Weber et al, 2016). This result was expected because, in the natural course of TBI, most spontaneous recovery occurs originally (Watson, 2007).…”
Section: Discussionsupporting
confidence: 94%
“…Evidently, GCS at discharge, length of hospital stay, and hydrocephalus were the major factors affecting the patient outcomes. Sandhaug, Andelic, Bernsten, Seiler, and Mygland (2011) and Sandhaug, Andelic, Langhammer, and Mygland (2015) revealed that the FIM results were improved in both moderate and severe TBI patients from admission until discharge from the rehabilitation unit. In the period between discharge and 12 months post-injury, the FIM-total and FIM-motor scores improved in severe TBI patients, but this was not for FIM-cognitive.…”
Section: Introductionmentioning
confidence: 97%
“…Sandhaug, Andelic, Bernsten, Seiler, and Mygland (2011) and Sandhaug, Andelic, Langhammer, and Mygland (2015) studied the 2-year post-injury functional outcomes of moderate to severe TBI cases in Norway. For the severe TBI cases, the FIM scores of all patients improved to a peak level between 3 and 24 months post-injury.…”
Section: Resultsmentioning
confidence: 99%
“…The article from Klemenc-Ketis et al (2011) also did not explain in detail the data collection process and ethical procedure. It was same with the articles retrieved from Sandhaug et al (2011) and Sandhaug et al (2015); in their studies, it was stated that they have an educational package for TBI survivors during the rehabilitation phase, but they did not explain about the package in detail. It would be great if could explain the detail of the educational package because it will help other researchers to adopt it in their future studies.…”
Section: Resultsmentioning
confidence: 99%